1995
DOI: 10.1007/bf00814232
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the reaction mechanism for the partial oxidation of methane to synthesis gas over platinum

Abstract: . M. M. (1995). An investigation on the reaction mechanism for the partial oxidation of methane to synthesis gas over platinum. Catalysis Letters,, 291-304. DOI: 10.1007/BF00814232 General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…The partial oxidation of methane to synthesis gas over platinum has been reported upon previously (32) and is summarized below. On reduced platinum the decomposition of methane results in the formation of carbon and hydrogen adatoms.…”
Section: Comparison Between Rhodium and Platinummentioning
confidence: 99%
See 2 more Smart Citations
“…The partial oxidation of methane to synthesis gas over platinum has been reported upon previously (32) and is summarized below. On reduced platinum the decomposition of methane results in the formation of carbon and hydrogen adatoms.…”
Section: Comparison Between Rhodium and Platinummentioning
confidence: 99%
“…Lapsewicz and Jiang (19) reported that methane activation is the rate-limiting step in the partial oxidation of methane. The difference in methane conversion can then be explained by the observed difference in apparent activation energy for methane activation on platinum, 52 kJ mol −1 (32), and rhodium, 15 kJ mol…”
Section: Comparison Between Rhodium and Platinummentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the ideas about the participation of various oxygen species in different elementary steps of this Pt-catalysed reaction were later confirmed by Fathi et al [11]. In contrast to Mallens et al [10], the latter authors ascribed CO formation to chemisorbed oxygen species formed either via O 2 dissociation or to oxygen atoms diffusing from the bulk of Pt to the surface. Direct participation of adsorbed oxygen molecules in oxidation of methanol and methane over Pt(1 1 1) has been also reported in literature [12,13].…”
Section: Introductionmentioning
confidence: 93%
“…The catalytic relevance of these oxygen species has been highlighted earlier for various Pt-catalysed reactions. Mallens et al [10] have shown that in partial oxidation of methane to syngas (CO and H 2 ) over polycrystalline Pt oxygen species of PtO x nature contributed to CO formation and its further oxidation to CO 2 . The role of adsorbed oxygen atoms was restricted to oxidation of CO to CO 2 .…”
Section: Introductionmentioning
confidence: 99%